Control of chronic Strongyloides stercoralis infection in an endemic community may be possible by pharmacological means alone: Results of a three-year cohort study. - Russell Hays; Adrian Esterman; Robyn McDermott (PLoS Neglected Tropical Diseases, 2017)
OBJECTIVES:To assess the effect of treatment with ivermectin on the prevalence of S. stercoralis infection in an Australian Aboriginal population over a three year period, and to assess the validity of using a lower ELISA cut-off in diagnosis. METHODS:A three-year cohort study of 259 adult Australian Aboriginals living in a remote community in northern Australia. S stercoralis infection was diagnosed using commercial ELISA testing, and employed a lower threshold for treatment than that recommended. Follow up was conducted at 6 months and 3 years following ivermectin treatment. FINDINGS:Treatment with ivermectin was highly effective and resulted in a sustained fall in the prevalence of infection in the study group (Initial prevalence 35.3%, 3 year prevalence 5.8%, McNemar's chi2 = 56.5, p<0.001). Results of treatment suggested use of a lower ELISA threshold for treatment was valid in this setting. Follow up identified a small group of subjects with persistently positive ELISA serology despite repeated treatment. INTERPRETATION:Control of S. stercoralis infection in this cohort appears to be feasible using pharmacological treatment alone.